An exploratory study of pacing and trajectories in elite open-water swimming using GPS and critical velocity modeling - Pla, R.; Bouvet, A. (Journal of Sports Sciences, 2026)
This study explores the use of GPS tracking to analyse pacing and trajectory patterns continuously throughout a 10-km open-water race. Five elite or world-class swimmers were monitored during the French National Championships using a global navigation satellite system device recording 1 Hz position data to assess latitude-longitude time series, distance, and modelled instantaneous swimming speed via locally estimated scatterplot smoothing. Based on individual critical velocity (CV), time and distance spent in four intensity zones ( <98%CV, 98-100%CV, 100-102%CV, >102%CV) were calculated. Substantial intra- and inter-individual variability in pacing intensity and race trajectories were highlighted over the race. Swimmers covered a median of 10,262 m[10259- 10,268], spending 619 m[593-632] >CV and 8585 m[8346-9183] <98%CV. Marked differences in pacing regulations were observed, with the race winner delaying high-intensity efforts until the end-spurt and managing intra-lap periodic accelerations around buoys and feeding stations while remaining <98%CV. Conversely, early and sustained periods >CV could be associated with poorer outcomes. Beyond traditional split-time analysis, combining high-resolution GPS devices with CV modelling enabled spatiotemporal profiling of race dynamics and individual behaviour, offering novel tactical insights into pivotal race moments, drafting use and related trajectory selection. Although exploratory, this proof-of-concept supports advanced performance analysis in open-water elite swimming.